2014
DOI: 10.4187/respcare.03123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Medication Adherence and Health-Related Quality of Life in Subjects With COPD: A Systematic Review

Abstract: BACKGROUND: Various aspects of medication adherence and health-related quality of life (HRQOL)have been studied in subjects with COPD. Nevertheless, little is known about the association between these factors. The aim of this study was to undertake a systematic review of the published literature focusing on the relationship between medication adherence and HRQOL in COPD. METHODS: A systematic literature search of English language articles was conducted in April 2013 using MEDLINE. No publication date limits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
5
42
0
1
Order By: Relevance
“…Consistent with findings of some other studies, our finding was that those with better self-rated general health had a lower prevalence of adherence, suggesting that in younger adults, self-appraisal of general health as “excellent” or “very good” may trigger nonadherence, possibly given that many in this age group have not developed physical CVD symptoms yet (28,29). Conversely, recent poor physical health also predicted a lower prevalence of high adherence, suggesting that physical disease symptoms may be associated with reduced adherence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with findings of some other studies, our finding was that those with better self-rated general health had a lower prevalence of adherence, suggesting that in younger adults, self-appraisal of general health as “excellent” or “very good” may trigger nonadherence, possibly given that many in this age group have not developed physical CVD symptoms yet (28,29). Conversely, recent poor physical health also predicted a lower prevalence of high adherence, suggesting that physical disease symptoms may be associated with reduced adherence.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, recent poor physical health also predicted a lower prevalence of high adherence, suggesting that physical disease symptoms may be associated with reduced adherence. Therefore, different domains of HRQOL may have distinct influences on adherence in younger adults, and future research must explicitly understand the mechanisms by which specific aspects of HRQOL influence adherence in this age group (29,30). In older adults, both poor physical health and poor health–related activity limitation were associated with lower prevalence of adherence, indicating that aging-related physical health symptoms and associated disabilities may be important barriers to adherence in older populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reviews, we found no clear association between non‐adherence and QoL . In a review specific to COPD medications, only 1 of the included studies measured the impact of adherence to nebulizers over a 4‐week period, finding that adherence was negatively correlated with disease‐specific HRQoL, measured at the end of the study .…”
Section: Discussionsupporting
confidence: 83%
“…In a review specific to COPD medications, only 1 of the included studies measured the impact of adherence to nebulizers over a 4‐week period, finding that adherence was negatively correlated with disease‐specific HRQoL, measured at the end of the study . The relationship between adherence and QoL can be influenced by many factors such as disease severity, cognitive functioning and the patient's understanding of their medication regimen . Therefore, to truly understand the complex relationship between adherence and QoL, multivariable regression analyses should be conducted, which were absent in most of the QoL studies included in this review.…”
Section: Discussionmentioning
confidence: 99%